1994
DOI: 10.1063/1.111401
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced conductivity of zinc oxide thin films by ion implantation of hydrogen atoms

Abstract: Enhancement of the conductivity of zinc oxide through doping with hydrogen atoms was examined by using ion implantation of highly resistive thin films deposited by rf magnetron sputtering at room temperature. With a doping of 1×1017 atoms cm−2, the conductivity after annealing at 200 °C in an N2 atmosphere at 1 atm rose from the initial 1×10−7 Ω−1 cm−1 to 5.5×102 Ω−1 cm−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 4 publications
3
40
0
Order By: Relevance
“…Mollwo [11] observed an increase in the conductivity of ZnO crystals exposed to hydrogen at temperatures above 200 ± C. The increase in the conductivity was demonstrated to be due to indiffusion of hydrogen, for which an activation energy of 0.91 eV was measured [11,12]. An increase in conductivity upon exposure to H 2 was also observed by Baik et al [14], and by Kohiki et al [15] who introduced hydrogen by proton implantation followed by annealing at 200 ± C. All of these experimental results indicate that introducing hydrogen into ZnO does not result in a reduction of the conductivity, which is the expected behavior for hydrogen in other semiconductors. Instead, H shows strong behavior as a donor, consistent with the calculations reported here.…”
Section: (Received 3 February 2000)supporting
confidence: 56%
“…Mollwo [11] observed an increase in the conductivity of ZnO crystals exposed to hydrogen at temperatures above 200 ± C. The increase in the conductivity was demonstrated to be due to indiffusion of hydrogen, for which an activation energy of 0.91 eV was measured [11,12]. An increase in conductivity upon exposure to H 2 was also observed by Baik et al [14], and by Kohiki et al [15] who introduced hydrogen by proton implantation followed by annealing at 200 ± C. All of these experimental results indicate that introducing hydrogen into ZnO does not result in a reduction of the conductivity, which is the expected behavior for hydrogen in other semiconductors. Instead, H shows strong behavior as a donor, consistent with the calculations reported here.…”
Section: (Received 3 February 2000)supporting
confidence: 56%
“…There are some reports on the effects of hydrogen ion implantation into Zn oxide films and Ge-Cd oxide films. [10][11][12] They confirmed that the hydrogen implantation improved the electrical conductivity of the oxides. The protium introduced into the oxides, however, sometimes gives coloration to the oxides.…”
Section: Introductionsupporting
confidence: 62%
“…Similarly, theory [1][2][3] suggests hydrogen is a shallow donor impurity rather than a compensating center, a prediction supported by a number of spectroscopic studies. 4 -14 Some electrical measurements [12][13][14][15][16][17][18] are also consistent with H donor character, although the polycrystalline samples, direct plasma exposure, or the ion implantation involved may introduce additional complications. This letter presents strong transport and spectroscopic evidence in favor of the hydrogen shallow donor hypothesis.…”
mentioning
confidence: 97%